A finite difference equivalent circuit approach to secondary current modelling in annular porous electrodes. Issue 2 (2001) - Farrell, T. W.; Mcelwain, D. L. S.; Swinkels, D. A. J.
Abstract : An equivalent circuit for an annular porous electrode is derived by reinterpreting the differential equations that approximate the distribution of voltage and current in such electrodes. The equivalent circuit is shown to provide useful physical interpretations of the secondary current distributions. Multi-loop circuit techniques are employed to obtain the current distributions within the circuit. The solutions are shown to compare well with the exact solutions of the model equations. In addition, the equivalent circuit approach is used to investigate the effect of curvature on the degree of polarization of the electrode.